2015
DOI: 10.1128/aem.02098-15
|View full text |Cite
|
Sign up to set email alerts
|

AllR Controls the Expression of Streptomyces coelicolor Allantoin Pathway Genes

Abstract: cStreptomyces species are native inhabitants of soil, a natural environment where nutrients can be scarce and competition fierce. They have evolved ways to metabolize unusual nutrients, such as purines and its derivatives, which are highly abundant in soil. Catabolism of these uncommon carbon and nitrogen sources needs to be tightly regulated in response to nutrient availability and environmental stimulus. Recently, the allantoin degradation pathway was characterized in Streptomyces coelicolor. However, there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…These results raise the question: why are ethylene glycol or glyoxylate not the effectors that bind GclR to relieve repression of the downstream metabolic genes? Clues to the answer can be found in the genomic context of the gclR gene in P. putida KT2440, which, similarly to other organisms such as Escherichia coli , Streptomyces coelicolor and Bacillus subtilis (Cusa et al ., ; Schultz et al ., ; Rintoul et al ., ; Hasegawa et al ., ; Navone et al ., ), encodes multiple genes known or predicted to be involved in the metabolism of purines via the intermediates allantoin and glyoxylate (Fig. A,C).…”
Section: Resultsmentioning
confidence: 99%
“…These results raise the question: why are ethylene glycol or glyoxylate not the effectors that bind GclR to relieve repression of the downstream metabolic genes? Clues to the answer can be found in the genomic context of the gclR gene in P. putida KT2440, which, similarly to other organisms such as Escherichia coli , Streptomyces coelicolor and Bacillus subtilis (Cusa et al ., ; Schultz et al ., ; Rintoul et al ., ; Hasegawa et al ., ; Navone et al ., ), encodes multiple genes known or predicted to be involved in the metabolism of purines via the intermediates allantoin and glyoxylate (Fig. A,C).…”
Section: Resultsmentioning
confidence: 99%
“…coelicolor [49]. However, further research has indicated that the impairment of antibiotic production was an indirect effect of the imbalance in nitrogen metabolism [50].…”
Section: Resultsmentioning
confidence: 99%
“…The expression of a number of genes related to nitrogen acquisition, such as glc - hyi - glxR (allantoin degradation), paaIK (phenylacetate degradation), blr6443/45-6447 and bll0913 (LIV transport), nirA (assimilatory NO 2 − reductase), and glnK 2 (nitrogen regulatory protein PII), was down-regulated (Table 2 and Fig. 2) (1, 6, 13, 21, 36). The PII protein encoded by glnB was also down-regulated in the Δ nasT mutant of Paracoccus denitrificans (17).…”
Section: Resultsmentioning
confidence: 99%